2018
DOI: 10.18633/biotecnia.v20i3.711
|View full text |Cite
|
Sign up to set email alerts
|

ACTIVIDADES BIOLÓGICAS DEL EXTRACTO METANÓLICO DE Rhodosorus marinus

Abstract: Las microalgas marinas pueden ser una fuente de moléculas bioactivas; existen numerosos reportes de actividad antioxidante, antibacteriana y antiproliferativa de extractos obtenidos a partir de macroalgas. El objetivo del presente trabajo fue evaluar la actividad citotóxica, antioxidante y antimutagénica del extracto metanólico de la microalga roja Rhodosorus marinus. El extracto fue obtenido a partir de biomasa liofilizada mediante lisis ácida y sonicación. Se evaluó la actividad citotóxica frente a 7 líneas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The variability depends on several factors during the growing conditions as the nutrients in the medium, age of culture, salinity and the solvent used for the extraction. The solvent had an important role in obtaining antioxidant pigments since each pigment is extracted in different quantities, due to polarity ( Baudelet et al, 2013 , Burboa-Zazueta et al, 2018 ). In our study, nitrogen deficiency and high salinities increased the chlorophylls and carotenoids content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variability depends on several factors during the growing conditions as the nutrients in the medium, age of culture, salinity and the solvent used for the extraction. The solvent had an important role in obtaining antioxidant pigments since each pigment is extracted in different quantities, due to polarity ( Baudelet et al, 2013 , Burboa-Zazueta et al, 2018 ). In our study, nitrogen deficiency and high salinities increased the chlorophylls and carotenoids content.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the concentration used in the extract of Nostoc muscorum that the inhibition test was higher (30 mg·mL −1 ) than that from our study (780 μg·mL −1 ). Recent studies have shown that organic solvents influence the obtention of antioxidant pigments from microalga because the % of inhibition performed in an aqueous extract is low for ABTS •+ and DPPH • as is the case of the microalga Rhodosorus marinus that showed 5.59 ± 0.63% ABTS •+ inhibition and 25.60 ± 4.03% DPPH • radical inhibition ( Burboa-Zazueta et al, 2018 ). However, in our case, the three pigment extracts (methanolic, acetonic, and ethanolic) presented low DPPH inhibition, probably attributed to composition.…”
Section: Discussionmentioning
confidence: 99%